Nursing practice environment and nurses’ satisfaction in a hospital context: a scoping review - Chen, Jun (2020)
Background: The evidence documents demonstrate a relationship between the nursing practice environment, the nurse´s satisfaction, the patient´s satisfaction with nursing care quality. Positive nursing practice environment increases levels of job satisfaction and human resources retention. As such, nurses play a crucial role in creating better nursing practice environments. Objective: The aim of Scoping Review is to map out and analyze work environment and nurses’ job satisfaction in hospitals. Inclusion criteria Types of participants: Registered and licensed practical nurses. Concept: Nursing practice environment and job satisfaction. Context: Hospitals. Search strategy: Using a version proposed by the Joanna Briggs Institute, following 3 research steps: 1) An initial research in CINHAL and MEDLINE; 2) A broader search using the keywords and search terms in the databases of the EBSCOHost platform; 3) Search in the bibliographic references of the selected articles. The time period between 2011 and 2016 was defined. Extraction of results: Two reviewers extracted data independently. Any disagreements between the reviewers. Twelve studies were included corresponding the criteria´s. Presentation of results: Twelve studies has documented the relationship among the nursing practice environment, nurse satisfaction, patient satisfaction and quality of care. The frequent reason for dissatisfaction of nurses is: high levels of burnout, job dissatisfaction, salary, and intention to leave. Research demonstrated the positive nursing practice environment increase levels of job satisfaction and staff retention of nurses. Discussion and Conclusions: Results showed a stable nurse workforce is associated with favorable perceptions of nursing practice environment factors, adequate workload, autonomy to make decisions and low levels of burnout.